Editorial: Insights in Ethnopharmacology: 2022 - Echeverria-Morgado, J (Frontiers Media SA, 2023)
[No abstract available]
Keywords: insights in ethnopharmacology: 2022; ethnomedicinal drugs; preventive strategy; therapeutic efficacy; phytochemicals; genomic sequencing technology; combinatory pharmacology